2014
DOI: 10.1210/jc.2013-3326
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Psychosocial Outcomes in Patients With Congenital Adrenal Hyperplasia: Epidemiological Studies in a Nonbiased National Cohort in Sweden

Abstract: This study shows important outcome differences regarding education; employment; marriage and fertility, depending on sex; and severity of CAH. The mechanisms behind this and the increased risk for sick leave or disability pension in both men and women should be identified to improve medical and psychological care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 38 publications
0
73
0
Order By: Relevance
“…These may use information from screening programs, hospital morbidity data, or data from specific disease registries or clinic samples, providing there are patient identifiers (such as date of birth) that are common to all datasets. In countries that operate a newborn screening program for CAH or have a national disease register, data can be linked to morbidity and mortality datasets and analyzed progressively, providing information on a wide range of outcomes [7, 66-69]. These can also be combined with other data sources, such as stored pharmaceutical prescription data, which can act as proxies for underlying diagnoses or even act as indices of severity [45].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…These may use information from screening programs, hospital morbidity data, or data from specific disease registries or clinic samples, providing there are patient identifiers (such as date of birth) that are common to all datasets. In countries that operate a newborn screening program for CAH or have a national disease register, data can be linked to morbidity and mortality datasets and analyzed progressively, providing information on a wide range of outcomes [7, 66-69]. These can also be combined with other data sources, such as stored pharmaceutical prescription data, which can act as proxies for underlying diagnoses or even act as indices of severity [45].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…However, other data also suggest that patients function normally and have a good overall psychological adjustment [5]. Most recently, a study of 588 CAH adults in Sweden showed that the total cohort of CAH patients did not differ greatly from the general population in terms of education, employment, income, sick leave, disability pension, social welfare, marriage, or children [6]. However, a subanalysis revealed that outcomes were worse among women and those affected with the classic form of the disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…Adults have identified experiences during their childhood that have negatively impacted them, including the processes involved in understanding or becoming aware of CAH, hospitalizations for adrenal crises, and surgical interventions to correct genitourinary conditions in females [4]. In contrast, a recent study of children with CAH in a Dutch population showed few negative effects of CAH on physical, social, and societal functioning based on a self-designed questionnaire [6]. Clearly, more research is needed to identify the aspects of a child's QOL that may be impaired.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Swedish follow-up studies investigating different aspects of long-term outcomes show that the most severely affected patients, the null genotype group, differ from the I2 splice genotype group, also causing the salt-wasting form of CAH, not only regarding outcome of genital surgery, but also regarding psychological aspects [13-18]. Females with CAH have an increased risk of negative effects regarding sexual function and reproductive potential, especially in the more severe cases, but it is unclear if this is the result of the degree of prenatal virilization or other factors related to the disease [13, 14, 18]. In addition, there is some evidence that women with the null genotype have lower results on measures of psychometric intelligence [15].…”
Section: Congenital Adrenal Hyperplasiamentioning
confidence: 99%